2021
DOI: 10.35907/bgjk.v12i2.178
|View full text |Cite
|
Sign up to set email alerts
|

Konseling Pada Ibu Yang Memiliki Balita Gizi Kurang

Abstract: Masa balita adalah masa emas ( golden age periode) karna pesatnya pertumbuhan dan perkembahan fisik motorik kasar dan motorik halus anak tersebut, dan saat ini masalah kesehatan yang utama di Indonesia yaitu masalah gizi. Dinas kesehatan kabupaten polewali mandar melaporkan tahun 2014 prevalensi keadaan gizi balita di kabupaten polewali mandar yaitu gizi buruk 153 (0,37%), gizi kurang 1.250 (3,44%), gizi lebih 204 (0,57%), BGM 870 (2,44%). Adapun permasalahan yang didapatkan di desa rumpa yaitu antara lain dar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In 2013, WHO reported that about 99 million children under the age of 5 suffer from malnutrition, of which 67% are in Asia and 29% in Africa. 3 Currently, the main public health issue in Indonesia is nutritional problem where the body experiences disturbances in nutrients necessary for growth, development and doing activity. This study uses various data from the Indonesian government.…”
mentioning
confidence: 99%
“…In 2013, WHO reported that about 99 million children under the age of 5 suffer from malnutrition, of which 67% are in Asia and 29% in Africa. 3 Currently, the main public health issue in Indonesia is nutritional problem where the body experiences disturbances in nutrients necessary for growth, development and doing activity. This study uses various data from the Indonesian government.…”
mentioning
confidence: 99%